Evaluation of a whole blood remote platelet function test for the diagnosis of mild bleeding disorders. (May 2014) - Dovlatova, N.; Lordkipanidzé, M.; Lowe, G. C.; Dawood, B.; May, J.; Heptinstall, S.; Watson, S. P.; Fox, S. C.; for the UK GAPP Study Group
Summary Background Mild platelet function disorders (PFDs) are complex and difficult to diagnose. The current gold standard test, light transmission aggregometry (LTA), including lumi‐aggregometry, is time and labour intensive and blood samples must be processed within a limited time after venepuncture. Furthermore, many subjects with suspected PFDs do not show a platelet abnormality on LTA. Objective To assess the diagnostic potential of an easy‐to‐use remote platelet function test (RPFT) as a diagnostic pre‐test for suspected PFDs. Methods A remote platelet function test was compared with lumi‐aggregometry in participants recruited to the Genotyping and Phenotyping of Platelets Study (GAPP, ISRCTN 77951167). For the RPFT, whole blood was stimulated with platelet agonists, stabilized with PAMFix and returned to the central laboratory for analysis of P‐selectin and CD63 by flow cytometry. Results For the 61 study participants (42 index cases and 19 relatives) there was a good agreement between lumi‐aggregometry and the RPFT, with diagnosis being concordant in 84% of cases (κ = 0.668, P < 0.0001). According to both tests, 29 participants were identified to have a deficiency in platelet function and 22 participants appeared normal. There were four participants where lumi‐aggregometry revealed a defect but the RPFT did not, and six participants where the RPFT detected an abnormal platelet response that was not identified by lumi‐aggregometry. Conclusion This study suggests that the RPFT could be an easy‐to‐use pre‐test to select which participants with bleeding disorders would benefit from extensive platelet phenotyping. Further development and evaluation of the test are warranted in a wider population of patients with excessive bleeding and could provide informative screening tests for PFDs.